Inertial Sensor-Based Assessment of Central Sensory Integration for Balance After Mild Traumatic Brain Injury - Gera, Geetanjali (Mil Med, 2018)
INTRODUCTION: Optimal balance control requires a complex integration of sensory information from the visual, vestibular, and proprioceptive systems. The goal of this study is to determine if the instrumented modified Clinical Test of Sensory Integration and Balance (mCTSIB) was impaired acutely after mild traumatic brain injury (mTBI) when postural sway under varying sensory conditions was measured with a wearable inertial sensor. MATERIALS AND METHODS: Postural sway was assessed in athletes who had sustained a mTBI within the past 2–3 d (n = 38) and control athletes (n = 81). Postural sway was quantified with a wearable inertial sensor (Opal; APDM, Inc.) during four varying sensory conditions of quiet stance: (1) eyes open (EO) firm surface, (2) eyes closed (EC) firm surface, (3) eyes open (EO) foam surface, and (4) eyes closed (EC) foam surface. Sensory reweighting deficits were computed by comparing the postural sway area in eyes closed versus eyes open conditions for firm and foam condition. RESULTS: Postural sway was higher for mTBI compared with the control group during three of the four conditions of instrumented mCTSIB (EO firm, EC firm, and EC foam; p < 0.05). Sensory reweighting deficits were evident for mTBI individuals compared with control group on foam surface (EC firm vs EO firm; p < 0.05) and not on firm surface (EC firm vs EO firm; p = 0.63). CONCLUSIONS: The results from this study highlight the importance of detecting postural sway deficits during sensorimotor integration in mild TBI individuals.